2018
DOI: 10.3390/ijms19123805
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of iNOS on Immune Cells and Its Role in Diseases

Abstract: In recent years, there have been many studies on the function of nitric oxide synthase (NOS) in experimental animals and humans. This review analyzes and explores the relationship between inducible nitric oxide synthase (iNOS) and T cells, macrophages, and dendritic cell et al. differentiation using data based on laboratory research, highlighting recent NOS laboratory research. Our insights into research prospects and directions are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
188
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(222 citation statements)
references
References 75 publications
5
188
1
2
Order By: Relevance
“…Previous studies showed that iNOS sourced from macrophages regulates M1 macrophage differentiation and the production of inflammatory cytokines usually produced by M1 macrophages, but this finding is not fully understood. 39 Therefore, the high levels of CD11b þ /iNOS þ cells in the lungs of C. gattii-infected mice identified on d 7 may impair M1 macrophage differentiation and the production of pro-inflammatory cytokines, as verified on d 14 and 21 post infection ( Figure 6). The effect of iNOS expression on the regulation of M1 macrophages produces a significant increase in CD11b þ /Arg-1 þ cells in the pulmonary tissue of infected mice on d 14 and 21 post infection.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Previous studies showed that iNOS sourced from macrophages regulates M1 macrophage differentiation and the production of inflammatory cytokines usually produced by M1 macrophages, but this finding is not fully understood. 39 Therefore, the high levels of CD11b þ /iNOS þ cells in the lungs of C. gattii-infected mice identified on d 7 may impair M1 macrophage differentiation and the production of pro-inflammatory cytokines, as verified on d 14 and 21 post infection ( Figure 6). The effect of iNOS expression on the regulation of M1 macrophages produces a significant increase in CD11b þ /Arg-1 þ cells in the pulmonary tissue of infected mice on d 14 and 21 post infection.…”
Section: Discussionmentioning
confidence: 76%
“…24,25 Thus, our findings suggest an important role of iNOS in the pathogenesis of C. gattii strain R265 that may be related to the maintenance of virulence, which may be supported by the 'division of labour' hypothesised by Voelz et al 25 or may be related to the effect of iNOS expression in the balance between M1 and M2 macrophages. 8,39 The current work indicates that the effect of inhibition and lack of iNOS on progression of C. gattii infection should be evaluated among distinct strains of mice.…”
Section: Discussionmentioning
confidence: 99%
“…NO is produced by three types of NO synthase (NOS): endothelial (eNOS), neuronal (nNOS), and inducible (iNOS) [39]. In the immune response, large amounts of NO are mainly produced by iNOS in response to cytokine stimulation [40]. In chronic inflammation, iNOS is thought to be involved in the formation of granulomatous lesions [41].…”
Section: Discussionmentioning
confidence: 99%
“…A pegylated form of the catabolic enzyme Arg I (peg-Arg I) can enhance the growth of tumors in mice in a manner that correlates with increased MDSC numbers through general control of the nonrepressed-2 eIF2α kinase [41]. NO can react with superoxide to form PNT and then directly inhibit T cells by nitrifying TCR, thereby reducing the affinity of TCR for antigen-MHC complexes presented by cancer cells and blocking the migration of T cells by nitrating T cell-specific chemokines [42,43]. The two major subpopulations of MDSCs exploit different mechanisms to inhibit T cell proliferation.…”
Section: Metabolic Mechanismsmentioning
confidence: 99%